1997
DOI: 10.3354/ame012011
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic degradation of phytoplankton debris dominated by Phaeocystis sp. in different physiological stages of growth

Abstract: ABSTRACT. The aerobic degradation of phytoplankton debris collected in Dutch coastal waters on 2 days in 1991 (15 April and 8 May), representing 2 physiological stages of a phytoplankton spring bloom dominated by Phaeocystis sp., was studied in batch culture experiments. The bacterial production and the concentrations of particulate organic carbon (POC) and dissolved organic carbon (DOC) were monitored over a period of 102 d. Bacterial numbers and biomass were followed for 35 d. All experiments showed a rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
(22 reference statements)
3
18
0
Order By: Relevance
“…The absence of acrylate is most likely due to rapid conversion, a finding that was also noted by Ansede et al (2), who, using nuclear magnetic resonance analysis, were unable to detect acrylate production by a Roseobacter species even though DMS was produced. The present results also agree with environmental studies that show rapid degradation of acrylate by bacterial communities associated with algal cells or debris (34).…”
Section: Discussionsupporting
confidence: 82%
“…The absence of acrylate is most likely due to rapid conversion, a finding that was also noted by Ansede et al (2), who, using nuclear magnetic resonance analysis, were unable to detect acrylate production by a Roseobacter species even though DMS was produced. The present results also agree with environmental studies that show rapid degradation of acrylate by bacterial communities associated with algal cells or debris (34).…”
Section: Discussionsupporting
confidence: 82%
“…Breakdown rates for mucopolysaccharides-The breakdown rate for mucopolysaccharides (50% in 11 d) was lower than that reported for the rapidly degradable fraction of Phaeocystis by Osinga et al (1997) (50% in 2-3 d). However, it is much higher than the rate they found for a slowly degradable fraction (80-99% in 1 yr).…”
Section: Effect Of Inhibitors On Mucopolysaccharide Degradation-mentioning
confidence: 62%
“…In addition, the relatively constant, complex composition of mucus carbohydrates throughout various spring blooms (Janse et al 1996a) could be interpreted as an indication for the absence of significant degradation. In the only direct study on the biodegradability of Phaeocystis, Osinga et al (1997) found that marine bacteria are able to degrade part of the Phaeocystis biomass. However, as degradation was only monitored by total organic carbon (TOC) measurements of nonpurified biomass, nothing could be concluded about the nature of the organic matter that was degraded or about the colony components it was derived from.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…With time, however, the composition and contribution of organic matter that can be utilized by bacteria will change from readily degradable freshly excreted DOM during the growth phase, to the DOM dominated by mucopolysaccharides and glucan during the senescent stage. In laboratory experiments it was shown that carbohydrates derived from P. globosa and P. pouchetii colonies were readily degraded by bacterial communities under both oxic and anoxic conditions (Osinga et al 1997;Janse et al 1999). The degradation rate of glucan was higher than that of mucopolysaccharides (Osinga et al 1997), but during degradation of the mucopolysaccharides the sugar composition of the mucopolysaccharides remained unchanged.…”
Section: Microbial Degradation Of Phaeocystis Carbohydratesmentioning
confidence: 99%
“…In laboratory experiments it was shown that carbohydrates derived from P. globosa and P. pouchetii colonies were readily degraded by bacterial communities under both oxic and anoxic conditions (Osinga et al 1997;Janse et al 1999). The degradation rate of glucan was higher than that of mucopolysaccharides (Osinga et al 1997), but during degradation of the mucopolysaccharides the sugar composition of the mucopolysaccharides remained unchanged. Therefore, there is no indication of refractory parts within the mucopolysaccharide fraction (Janse et al 1999).…”
Section: Microbial Degradation Of Phaeocystis Carbohydratesmentioning
confidence: 99%